Sustainable Mobility in the Cities and Agglomeration Areas - Jakub Majewski (Studia Ecologiae et Bioethicae)
The aim of this publication is to present the relationship between the dominant forms of urban mobility and the environmental pressures of the transport sector as well as the quality of life of the inhabitants of large cities and urban agglomerations. The presentation of trends and scenarios is based, on the one hand, on statistics describing current development trends and, on the other hand, on scenarios, recommendations, and commitments defined in European, national, and local governmental documents programming the socio-economic development of urbanised areas and the directions of climate transformation in their area. The article consists of a brief introduction, background on the latest regulations in the field of sustainable urban mobility, and a comparative analysis of environmental demands, along with actual trends observed in the transport sector in urbanised areas. It closes with conclusions relating to the validity and effectiveness of current transport and environmental policies, and recommendations, whilst identifying areas and instruments that increase the likelihood of achieving the stated objectives.